Occurrence and public-perceived risk of endocrine disrupting compounds in drinking water - Sze Yee, Wee; Ahmad Zaharin, Aris (Nature Portfolio, 2019)
Access to safe water is a crucial factor in determining environmental sustainability, public health, and economic prosperity. Endocrine disrupting compounds (EDCs) are an environmental contaminant of growing concern, which undermine the safety of drinking water. The potential health issues of EDCs are not fully understood yet due to there being relatively scarce research on their exposure and associated risks via drinking water consumption. Because of ineffective drinking water supply systems and unknown risk perceptions of EDCs in drinking water, the role of perceived risks in ensuring access to safe drinking water remains unknown, contributing to the occurrence of such potential risks in the global water system. Integrating preventive measures with a multibarrier approach to safe drinking water is highly challenging because of the relatively low public awareness and political responsibility, as well as the nature and characteristics of EDCs themselves. In addition to reviewing the occurrence and publicperceived risks of EDCs in drinking water, this article focuses on building bases of knowledge and awareness for a better understanding of drinking water quality issues relative to the hazards surrounding EDCs from the perspectives of human exposure and health risk. A conceptual model illustrates the factors that potentially influence risk perception on drinking water quality in regard to not only EDCs but also other issues. Ensuring safe access to drinking water requires interventions that incorporate risk communication and governance, providing insights into political, economic, social, and environmental changes.